Perkembangan Akhir Masa Anak-Anak - Jumadilla Afifah; Oriza Latifah; Imah Yulianti; Linda Yarni (Universitas Palangka Raya, 2024)
Late childhood development is a continuation of early childhood. This period lasts from the age of 6 until the child becomes sexually mature. The beginning of late childhood is marked by the child's entry into the first grade of elementary school which is an important event for the child that can lead to changes in attitudes, values and behavior. In education, it can be adjusted by compiling materials, methods, facilities, and tools that are in accordance with the situation and conditions of the students. For parents, the growth and development of children and the service model will be known so that children can undergo developmental tasks and adapt to their environment well. The purpose of the analysis is to identify the characteristics of the end of childhood, analyze the developmental tasks of the end of childhood, and identify physical development at the end of childhood. Using the literature study method with an approach that involves analyzing relevant literature or information sources. In conclusion, the characteristics of development in late childhood, namely: a. Emotional development such as heightened emotions, the beginning of emotional catharsis, forming gangs of children; b. Game patterns such as exploring, constructive play, watching TV; c. Common offenses often occur such as fighting with siblings, shirking responsibilities, telling false lies. Physical development in late childhood includes: Height and weight, Motor development, Body ratio, Simplicity, Muscle-fat ratio, Teeth.